Palliative embolization of renal tumors - Jaganjac Suad; Schefe Lennart (Vojnosanitetski Pregled, 2015)
Background/Aim. Palliative embolization of renal tumors is the method of choice in the treatment of advanced inoperable renal cell carcinoma in patients with hematuria and pain. Patients with small tumors in the remaining solitary kidney who refuse surgery are suitable for this type of therapy as well as patients with centrally located inoperable tumors. The prerequisite for successful capillary embolization is the closure of the main arte-rial trunk with metal spirals. Methods. In the period from 2000 to 2010 we conducted 42 palliative embolizations. The average age of the patients was 75 years, including 26 men and 16 women. In 8 of the patients the intervention was repeated and in one with severe AV shunts embolization was performed 4 times. Embolization was performed with alcohol, Ivalon 150-250 μm and with metal coils. Results. No serious complications were observed during and after the intervention. Fourteen patient were still alive then and among the deceased patients the average survival time was 13.5 ± 10.8 months with the range of 1 to 56 months. The minimal survival time was 1 month with a maxi-mum survival time of 56 months. Conclusion. Our results are consistent with data in the literature. Survival in patients without metastases was longer than in those with metastases, as con-firmed by the 14 of the patients from the study. An additional therapeutic safety in the treatment of small cancers is provided with a combination therapy of embolization and radiofrequency thermoablation.